Expanding the application of positive education to non-formal settings through training nonformal education teachers - Dolev, Niva; Levi, Yifat (Frontiers in Education, 2025)
IntroductionPositive education is increasingly applied to foster the wellbeing of students and professional staff in schools, but its application in Non-Formal Education (NFE) remains underexplored. Given its flexible, value-driven and social nature, NFE frameworks could offer a particularly suitable setting for such application.MethodsThe study examined the experiences of 21 NFE teachers who participated in a nine-session positive education training program, aiming to identify whether and how the training contributed to their wellbeing and to the integration of positive education within their respective NFE frameworks. Qualitative data was collected from multiple sources, including interviews, reflection logs, WhatsApp correspondence and future work plans, and analyzed using inductive thematic analysis approach.ResultsThe program was found to produce a multidimensional increase in teachers’ wellbeing, enhancing positivity, self-awareness, self-compassion, self-efficacy, and a sense of professional meaning. It further motivated participants to integrate positive education elements into their teaching goals and to flexibly adapt such elements into their own NFE routines. Despite noted challenges, participants viewed NFE as a highly suitable setting for cultivating positive education, and suggested ways of adapting it for better integration.DiscussionIt is concluded that the integration of positive education into NFE teacher training programs could further its application, enhancing wellbeing among teachers and students. It is recommended that future training programs should focus on context-specific NFE practices which can be adapted and applied flexibly.